Vulnerability, climate change and livestock - opportunities and challenges for the poor - Thornton, Philip K.; Herrero, Mario; Freeman, H.A.; Okeyo Mwai, Ally; Rege, J.E.O.; Jones, Peter G.; McDermott, John J. (2007)
Livestock systems in developing countries are characterised by rapid change, driven by factors such as population growth, increases in the demand for livestock products as incomes rise, and urbanisation. Climate change is adding to the considerable development challenges posed by these drivers of change. How can livestock keepers take advantage of the increasing demand for livestock products, where this is feasible, and how can the livestock assets of the poor be protected in the face of changing and increasingly variable climates? Given the complexity of livestock and crop-livestock systems, a mix of technological, policy and institutional innovations will inevitably be required. Here we outline some of the likely impacts of climate change on livestock and livestock systems, and discuss some of the resultant priority livestock development issues: water and feeds, livestock genetics and breeding, and animal health. We highlight livestock's role in alleviating poverty and helping households to deal with climate variability. However, there are considerable gaps in our knowledge of how climate change and increasing climate variability will affect livestock systems and the livelihoods of the people who depend on them. We highlight the need for detailed assessment of localised impacts, and the importance of identifying appropriate options that can help livestock keepers adapt to climate change.